2016
DOI: 10.1002/1873-3468.12452
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor reduces CXCL10 expression in keratinocytes

Abstract: Keratinocytes secrete vascular endothelial growth factor (VEGF) and angioregulatory chemokines during cutaneous wound healing. Hepatocyte growth factor (HGF) promotes skin re-epithelialization by increasing VEGF expression in keratinocytes. Here, we investigated the regulatory roles of HGF in the expression of genes encoding angiogenic and angiostatic chemokines in keratinocytes and found that HGF specifically inhibits mRNA expression of the angiostatic chemokine CXCL10 in both mouse primary keratinocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Mouse Grp78 CTGCTGAGGCGTATTTGGGA and TCGCTGGGCATCATTGAAGT; mouse CHOP AATAACAGCCGGAACCTGAGG and CTCATACCAGGCTTCCAGCTC. Sequences of primers for human CXCL10 , mouse Cxcl10 , human HPRT , mouse Hprt were described previously 16 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mouse Grp78 CTGCTGAGGCGTATTTGGGA and TCGCTGGGCATCATTGAAGT; mouse CHOP AATAACAGCCGGAACCTGAGG and CTCATACCAGGCTTCCAGCTC. Sequences of primers for human CXCL10 , mouse Cxcl10 , human HPRT , mouse Hprt were described previously 16 …”
Section: Methodsmentioning
confidence: 99%
“…Sequences of primers for human CXCL10, mouse Cxcl10, human HPRT, mouse Hprt were described previously. 16 2.6 | Preparation of cell lysates, nuclear extracts, and plasma membrane fractions Cells were lysed in PLC buffer (50 mM HEPES [pH 7.0], 150 mM NaCl, 10% glycerol, 1.0% Triton X-100, 1.5 mM MgCl 2 , 1 mM EGTA, 10 mM sodium pyrophosphate, 100 mM NaF, and 1 mM sodium orthovanadate) containing protease inhibitors or RIPA buffer (20 mM Tris-HCl [pH 7.5], 150 mM NaCl, 1 mM ethylenediaminetetraacetic acid (EDTA), 1 mM EGTA, 1% NP-40, 1% sodium deoxycholate, 2.5 mM sodium pyrophosphate, 1 mM β-glycerophosphate, 1 mM Na 3 VO 4, 1 μg/ml leupeptin), and centrifuged at 12,000g to collect supernatants as cell lysates. For the preparation of nuclear extracts, cells were scraped from dishes in PBS(−), pelleted washed in hypotonic buffer (10 mM HEPES buffer [pH 7.9], 1.5 mM MgCl 2 , 5 mM KCl, 1 mM phenylmethylsulfonyl fluoride [PMSF], 1 mM dithiothreitol), and lysed by resuspension in the same buffer with 0.1% Nonidet P-40.…”
Section: Quantitative Real Time Rt-pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…HGF has been reported to modulate the inflammatory environment and enhance wound healing and regeneration in animal models of inflammation-associated diseases, including a skin inflammation model [ 17 ], multiple sclerosis model [ 18 ], pulmonary artery hypertension model [ 19 ] and bronchiolitis obliterans model [ 20 ] . HGF can mediate wound healing by accelerating the regeneration of epithelial cells [ 21 , 22 ] and by maintaining normal immune function [ 17 ]. Clinical data have shown that HGF gene therapy can significantly decrease the size of ulcers in patients with critical limb ischemia [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%